INFLASI SEBAGAI PEMODERASI HUBUNGAN CSR, LEVERAGE, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS DI SEKTOR CONSUMER CYCLICAL - Febriani, Kharisma; Rahmatika, Dien Noviany; Astutie, Yanti Puji (Catholic University Musi Charitas, 2026)
Purpose: This study investigates the influence of Corporate Social Responsibility disclosure, leverage, and sales growth on financial distress, with inflation as a moderatingvariable, focusing on consumer cyclical companies that are highly sensitive to economicfluctuations.Design Methodology Approach: A quantitative approach was applied using secondary data derived from the annual reports of consumer cyclical companies listed on the Indonesia Stock Exchange. Inflation data were obtained from the Central Bureau of Statistics. Data analysis was conducted using ordinal logistic regression and moderated regression analysis with SPSS.Findings: CSR disclosure significantly reduces the likelihood of financial distress, while leveragesignificantly increases it. Sales growth shows no significant direct effect. Inflation does notmoderate the relationship between CSR or leverage and financial distress; however, itsignificantly moderates the relationship between sales growth and financial distress.Practical Implications: Strengthening CSR initiatives and managing debt levels are crucialstrategies for mitigating financial distress risk, particularly in sectors exposed to macroeconomicvolatility.Originality Value: This study extends prior research by providing empirical evidence oninflation’s moderating role in the nexus between firm specific factors and financial distress in amacroeconomically sensitive industry, an area that has received limited attention in emergingmarket contexts.